Which Role Model Is More Effective in Entrepreneurship Education? An Investigation of Storytelling on Individual’s Entrepreneurial Intention - Liu, Feng; Ma, Jiangshui; Li, Ran (Frontiers in Psychology, 2019)
Entrepreneurial stories, such as the breathtaking experiences of Steve Jobs, are often adopted as an effective teaching instrument to promote individuals’ entrepreneurial intentions in entrepreneurship education. Prior research highlights the role model's influence and the positive effect of entrepreneurial stories is taken for granted in many circumstances. Since most researches treated storytelling in teaching as an undifferentiated whole, few researches have teased out the distinctive effect from different types of entrepreneurial stories, namely stories between successful stories and failure stories, and stories between idol stories and peer stories. To deepen our knowledge about how distinctive entrepreneurial stories effect on entrepreneurial intentions, we conducted two experimental studies on 150 undergraduate students in entrepreneurship education programs. Results show that, through the intermediary variable of entrepreneurial passion, both successful stories and failure stories positively influence entrepreneurial intentions as educators presumed, but successful role model stories have a greater impact than failure stories. While, rather than the idol stories, peer stories are more inclined to arouse individuals’ entrepreneurial intentions. Furthermore, we find that individuals with low entrepreneurial self-efficacy are less affected by storytelling process.